Taxonomy of the Cixiidae (Hemiptera, Fulgoromorpha) from the Madeira archipelago - Freitas, Énio; Aguín-Pombo, Dora (European Journal of Taxonomy, 2021)
Ninety percent of the Cixiidae of the Macaronesian archipelagos are endemic. Each archipelago has its own endemics reaching a total of 31 taxa. The Madeira archipelago comprises five species: Cixius madeirensis China, 1938, C. verticalis Noualhier, 1897, C. chaoensis China, 1938, Hyalesthes madeires Remane & Hoch, 1986 and H. portonoves Remane & Hoch, 1986. Good knowledge concerning taxonomy, habitat information and distribution are essential for the conservation of the biodiversity of this rich archipelago. However, due to intraspecific variation and incomplete descriptions, misidentifications of Madeira cixiids have been common. In this work, the taxonomy of this family is reviewed and ecological data based on material collected over more than forty years are presented. A new species, Cixius wollastoni sp. nov., is described. A new combination, Tachycixius chaoensis (China, 1938) comb. nov., is proposed, and a new record, Pentastiridius leporinus (Linnaeus, 1761), is reported. Lectotypes are designated for Tachycixius chaoensis and C. verticalis. The genital structures of the latter species are depicted for the first time. All species are diagnosed, described, photographed and illustrated, and an identification key for the family is provided. Thanks to this new information, Madeira together with Tenerife are the two Macaronesian islands with the highest number of endemic species of cixids.